Information needs and library services delivery for students with visual impairment in Oyo State, Nigeria (2018)
This study investigated the information needs and library service delivery to students with visual impairment in Oyo State, Nigeria with a focus on assessing the influence of library services; information needs; media formats availability and accessibility on library use among students with visual impairment in Oyo State, Nigeria The survey research design of the ex-post facto type was adopted for the study. The total enumeration method was used in selecting the sample size of 84 students out of which only 54 responded to the questionnaire. The study established educational information, health information and information on coping with their visual impairment as major information needs of the visually impaired students while circulation service, reference service and screen reading service on computers are found to be the only library services provided for them. Print Books/Magazines, Braille Books and Braille-in- Print were found to be prominent among the few media-format available for the students which the dearth of media-formats adequate in meeting the information needs of students with visual impairment in Oyo State. Lack of ease of accessing the circulation desk, lack of ease of accessing the entrance stairs, lack of; access to library staff whenever they need help, ease of finding their way around the library, guaranteed borrowing privileges within the library, path sounders to guide their movement around the library, smooth non-slip surfaces to prevent fall, unrestricted access to information resources media-format and lack of familiarity with the furniture and fittings in the library were major accessibility issues confronting the students in enjoying quality library services. Major purposes of using the library by the students are reading of educational Braille materials, completion of class assignments, reading for examinations and using of talking books. A positive relationship was established between library use and information needs, library service delivery, media formats availability and accessibility just as information needs, library service provision, library service delivery, accessibility and media format availability were found to have significant joint contribution to library use. The study recommended the need to address the provision of basic facilities that are critical to effective library service delivery to the visually impaired students.